PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KINERJA GURU TERHADAP EFEKTIVITAS SEKOLAH PADA SMA NEGERI 2 REJANG LEBONG BENGKULU - Aris Dianto (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2023)
This study aims to measure the influence of principal leadership and teacher performance on school effectiveness. This study obtained data from 60 educators who served as respondents at SMA Negeri 2 Rejang Lebong. Data obtained by questionnaire and processed using SPSS software. From the research it was found that leadership (X1) and teacher performance (X2) significantly influence school effectiveness (Y) with F count = 13.807. The school principal's leadership and teacher performance variables contribute to increasing the value of school effectiveness (Y), this can be seen from the value of the determinant index (R2), which is 0.303 or 30.3%.